Trade Unionism in the Cut Flower Industry in Kenya. A Case of Kenya Plantation and Agricultural Workers Union (KPAWU) - Kabiru, Joseph G. (European Scientific Journal, ESJ, 2018)
Trade unionism in the cut flower industry has been in existence since independence. Immediately after independence, there was an amalgamation of four labour unions which represented workers in different sub-sectors within the agricultural sector. As a result, the representation of workers’ labour issues in the agricultural sector was given to only one labour union called Kenya Plantation and Agricultural Workers Union (KPAWU). Since the formation of KPAWU, scholars have enumerated different challenges, both from within and without, that affected the union in fulfilling its mandate to its workers. This article attempts to measure the extent to which the KPAWU has contributed to workers’ welfare in the cut flower industry which is one of the sub-sectors in the agricultural sector. Literature review was done on historical development of labour unions in the agricultural sector in Kenya. Further, a comparative survey was used to study workers’ welfare in three Kenyan regions which were selected for this study, which are Naivasha, Nanyuki and Thika. Quantitative techniques were used to collect and analyse survey data. These quantitative techniques were supplemented by qualitative data from key informants (KIs) and Focus Group Discussions (FGD). Both univariate and bivariate methods of analysis were used in this study. The article establishes that trade unionism in the cut flower industry in Kenya had experienced several challenges both internal and external, like funding, poor skilled leadership and low membership registration, which have affected its growth. Currently, there is low registration of workers and poor funding of the trade union activities. Therefore, workers in the field were unsatisfied with the union. Thus, this article concludes that there is a correlation between the challenges experienced in the initial establishment of KPAWU and its contribution to workers’ welfare